5x+2y=3x-6

Simple and best practice solution for 5x+2y=3x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+2y=3x-6 equation:


Simplifying
5x + 2y = 3x + -6

Reorder the terms:
5x + 2y = -6 + 3x

Solving
5x + 2y = -6 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
5x + -3x + 2y = -6 + 3x + -3x

Combine like terms: 5x + -3x = 2x
2x + 2y = -6 + 3x + -3x

Combine like terms: 3x + -3x = 0
2x + 2y = -6 + 0
2x + 2y = -6

Add '-2y' to each side of the equation.
2x + 2y + -2y = -6 + -2y

Combine like terms: 2y + -2y = 0
2x + 0 = -6 + -2y
2x = -6 + -2y

Divide each side by '2'.
x = -3 + -1y

Simplifying
x = -3 + -1y

See similar equations:

| 5x+2(x-20)=380 | | 3x^3+3x^2+4x=16 | | 2x+(x+60)+(3x-30)=180 | | 0.6g+11=-5 | | X/a-1= | | 7.8/7.41 | | 5a+(2a-5)-(a-3)=16 | | 7(4y-9)-(4y+8)= | | b^2-7b-36=0 | | (e-b)(c-d)= | | 21-6x=9 | | -243^(3/5) | | 3y-1+2x-4+x+3+15= | | 8x+46=5(x+5) | | 3n-4l= | | 6x^2=15 | | 6.1x-1.5=10.7 | | 2x+4=12+x | | (3^√7y^5)/(3^√64x^6) | | 6(4z-1)-5(z+3)=12(z+1) | | 4+7(x-1)=4-9(x-5) | | 9z-5=16+6z | | (y^2+4)=2y^2-y-10 | | 4*(2x-3)=5(x+2) | | v=(1/3)pir^2h | | 3n-17=-19+4n | | -8*(8-1)=-16 | | x^2+6*x-3600=0 | | 1.5m+1.0m=7.5 | | 0=4(x^2+49)(x^2-36)(x-7) | | 1/5n=3.1 | | 18=3z+17 |

Equations solver categories